Corporate Governance and Stock Returns: Evidence from the S&P 500 - Owala, Anthony (My University, 2010)
This study analyzes the correlation between stock returns, corporate governance, and difference in stock returns between the good and weak governance portfolios. The analysis is based on the updated corporate governance index of Gompers, Ishii and Metrick (2003) and the stock returns of the S&P 500 firms for year 2008. The good and weak governance portfolio was built and had their stock returns average analyzed and compared following the Gompers approach. A cross-sectional analysis indicated that there was no significant difference in stock returns between the good and the weak governance portfolios. The analysis also reported that the level of corporate governance was insignificant in predicting stock returns. The report on stock returns correlation with corporate governance was negative, which revealed that returns were higher for the good governance firms. Consequently, the overall analyzes report was contrary to the study hypotheses. Finally, the relationship between stock returns, corporate governance, and control variables was also examined and the major findings were not consistent with the previous.
Keywords: Corporate Governance; Stock Returns; Corporate Governance Ratings; Good Governance Portfolio; Weak Governance Portfolio.; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|